An In Vivo study to compare and evaluate the correlation of the facial measurements with the combined mesiodistal width of the maxillary anterior teeth between males and females - Reshma Banu; Savita Dandekeri; K Kamalkanth Shenoy; Sanath Shetty; Vidya Bhat; Mallikarjuna Ragher (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study was to compare and evaluate the correlation of the facial measurements (interalar, intercommissural, intercanthal, and interpupillary distance) with the combined mesiodistal width of the maxillary anterior teeth between males and females. Objectives: The objectives of this study were: (a) To evaluate the correlation of the facial measurements (interalar, intercommissural, intercanthal, and interpupillary distance) and combined mesiodistal width of maxillary anterior teeth. (b) To compare the correlation of the facial measurements (interalar, intercommissural, intercanthal, and interpupillary distance) with the combined mesiodistal width of maxillary anterior teeth between males and females. Materials and Methods: This study was carried out on 120 dentate Subjects selected from Yenepoya Dental College, Mangalore. The vernier caliper was used to measure the interalar, intercommissural, intercanthal, and interpupillary distance. The mesiodistal width of maxillary anterior teeth was measured on the cast. For accuracy, every distance was measured three times and the mean taken. Results: Comparison of parameters between males and females was calculated using independent sample t-test. The values obtained for each variables are interalar distance: for males 38.89 ± 2.19 and for females 35.58 ± 2.33. Intercommissural distance: for males 50.96 ± 2.99 and for females 47.15 ± 2.97. Intercanthal distance: for males 31.92 ± 1.46 and for females 30.46 ± 2.07. Interpupillary distance: for males 65.15 ± 2.82 and for females 61.78 ± 3.18. Mesiodistal width of maxillary anterior teeth: for males 52.55 ± 1.82 and for females 51.33 ± 2.50. Conclusion: Within the limitations of this study, the study concluded there is a significant correlation between interalar, intercommissural, intercanthal, interpupillary distance, and mesiodistal width of maxillary anterior teeth in total subjects. In females, there is a significant correlation between interalar, intercanthal, interpupillary distance, and mesiodistal width of maxillary anterior teeth.